The Role of Telemedicine in Transforming Healthcare Delivery (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Telemedicine is vital for enhancing healthcare access, convenience, and efficiency. It overcomes traditional barriers by enabling people in remote or underserved areas to receive care without extensive travel, addressing provider shortages in isolated regions. It also supports vulnerable populations (those who are elderly or have a disability or chronic conditions) who find in-person visits difficult. Telemedicine facilitates follow-up care and chronic disease management using mobile apps and wearable devices for obtaining real-time patient data. This remote monitoring improves outcomes and reduces hospital readmissions. Implementation Challenges and Key Focus Areas: Effective implementation requires addressing healthcare disparities, reimbursement policies, and patient access to technology and training. Despite these hurdles, telemedicine is an essential tool globally. This Special Issue focuses on the following topics: Patient Education: Informing patients about benefits and availability; Provider Training: Equipping staff for virtual exams, platform use, and privacy; Remote Monitoring: Using devices to collect data for chronic condition management; Workflow Optimization: Streamlining scheduling for efficient appointments; Telemedicine Apps: Developing user-friendly apps for scheduling, reminders, and records; Emergency Protocols: Establishing clear procedures for virtual appointment emergencies.